Clustering of Futsal Interest Level Among Students K-Means Method - Bagaswara, Faris; Muthalib, Muchlis Abd; Meiyanti, Rini (International Journal of Engineering, Science and Information Technology, 2025)
Futsal is a small field sport with a time of 20 minutes per round. Malikussaleh University is one of the universities that initiated Futsal as a health sport for its students. To determine students' interest in Futsal, clustering was carried out using the K-Means method on 100 students of the Faculty of Engineering involved in this study. This research proposal uses five variables: time variables, field facilities, motivation, environment, and plans. This study aims to help students at Malikussaleh University of Engineering find out what level of interest students have in Futsal. Grouping is based on data mining to determine the pattern of each sequence. Data mining includes tracking patterns, classification, association, outlier detection, clustering, regression, and forecasting. This study also led to an innovative grouping system using the Python programming language and MySQL as a database. The K-Means Clustering algorithm used in this grouping system states that out of 100 Malikussaleh University students, 20 people are students who have a professional player futsal interest level (C1), 28 students have a regular player futsal interest level (C2), five students have a Beginner player futsal interest level (C3), 47 students have an amateur player futsal interest level (C4). The study results showed that 20% were professional, 28% were regular, 5% were beginner, and 47% were amateur players. These results indicate that the interest in Futsal for Malikussaleh University students is still minimal, so encouragement is needed for students to participate in futsal activities.